Establishing legal identity for displaced Syrians - Clutterbuck, M; Cunial, L; Barsanti, P; Gewis, T (Refugee Studies Centre, University of Oxford, 2018)
Seven years of conflict have had a serious detrimental effect on many Syrians’ ability to prove their legal identity.